Amino acid uptake in the developing chick embryo heart. The effect of insulin on glycine and leucine accumulation - Guidotti, G. G. (1968)
1. The accumulation of [1-(14)C]glycine and the uptake, accumulation, incorporation (into protein, lipid, glycogen) and oxidation of l-[1-(14)C]leucine in 5-day-old chick embryo hearts were investigated in vitro, and the effects of insulin, puromycin and 4-methyl-2-oxopentanoic acid on these processes were studied. 2. With glycine, the ratio of concentration of the labelled amino acid in the cell water to that in medium markedly exceeded unity. Insulin significantly increased this ratio. Puromycin did not prevent the insulin effect. 3. With leucine, the concentration ratio of the labelled amino acid between intracellular and extracellular water approached unity in the absence of puromycin and was doubled by its presence. In neither case did insulin substantially alter this ratio. The addition of 4-methyl-2-oxopentanoic acid had no effect in the absence of insulin, but produced a significant increase of the concentration ratio in the presence of the hormone. 4. Leucine uptake was increased slightly by insulin in all experimental conditions except in the presence of puromycin, where a more pronounced stimulation was observed. The hormone had no effect on the incorporation of the labelled amino acid into protein, but accelerated its oxidation to carbon dioxide; the latter effect was particularly evident in the presence of puromycin and disappeared after the addition of 4-methyl-2-oxopentanoic acid.